PERAN SATRATEGIS SISTEM EKONOMI ISLAM DALAM MEMBANGUN SUMBER DAYA INSANI - Misbahul (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2014)
One variable that very important in economic management is human resources. He was a strategic position and most decisive in the economic system of Islam. The potential and its position should be understood properly developed so he can optimally in order to strengthen the economic system of Islam. Islamic Human Resources it is the energy or power or ability of which is owned by someone thought of power, southwest of copyright, still stored karsa and work in itself as a potential energy ready to be developed into useful energy in accordance with human desire itself. In understanding of islam , all the potential is a device that provided by god as caliph mandate to run in the earth. Thus he is responsible for managing the best possible to achieve the welfare of the earth together. Characteristics that needed to support that task. That characteristic inspired by the nature of the prophets as honest, amanah, convey and smart , also the nature of such as courage and professional. If the preparation of resources that has characteristics insani above can be achieved, really potential of islam in the economic system can be developed beyond what can done by the system Islamic outside.